(Intermittent) Poverty and Peace in Guinea-Bissau - Rodrigues, Cristina (2011)
The research on the correlations between poverty and conflicts in Guinea-Bissau has allowed to put in evidence not only the direct implications of the effective war of 1998/1999 over the living conditions of the country’s population, as well as the effects the conflicts - either effective or eminent – have over life in general, individual investments of different kinds and on reliance on the state and institutions. Although the fundamentally qualitative investigation highlighted the diversity of individual and family situations, it allowed identifying a denominator seen as common in most of the collected accounts : war and, in the case study of Guinea-Bissau, the perpetuation of an insecure environment, constitute causes for the increase in poverty and concur simultaneously to its reproduction through time.